Recent Advances in the Low-Temperature Chemical Vapor Deposition Growth of Graphene - Josline, Mukkath Joseph; Kim, Eui Tae; Lee, Jae Hyun (Applied Science and Convergence Technology, 2022)
Since the realization of the prospect of synthesizing graphene via mechanical exfoliation, graphene has garnered considerable attention owing to its remarkable chemical, electrical, material, and various other properties, which makes it an ideal contender for electronic and optoelectronic applications. Many top-down and bottom-up strategies have been researched to fabricate graphene films, notably chemical vapor deposition (CVD), which has been proven to deliver large-area, high-quality graphene films with the additional advantage of being economical. However, graphene production utilizing gaseous predecessors, such as methane, typically requires high temperatures, which increases the production cost due to the high thermal budget. Recently, the prospect of employing low-temperature conditions for graphene growth has been explored, using various hydrocarbon precursors and alternative energy sources. This review discusses the low-temperature CVD growth of graphene and recent improvements in this area with a brief introduction to applications based on these graphene specimens.
Keywords: Chemical vapor deposition; Electronic; Graphene; Low-temperature growth; Optoelectronic applications